A rare case of pulmonary mucormycosis complicated by hydropneumothorax, successfully treated with non‐surgical therapies. Issue 6 (12th May 2022) - Liu, Qiliang; Good, William; Salmon, Andrew; Gow, Nicholas; Griffiths, Paul
Abstract: Pulmonary mucormycosis (PM) is a rare but rapidly progressive fungal infection associated with high mortality. A review of the literature suggests that pleural effusions and pneumothoraces are uncommon manifestations associated with distant dissemination. Combined surgical interventions and prolonged antifungal therapy constitute the standard first‐line management, with significantly poorer outcomes seen in patients managed with medical therapy alone. Here, we report an unusual case of PM complicated by hydropneumothorax in an immunocompromised patient, in whom comorbidities and disease burden precluded surgical debridement. His disease was ultimately treated with intravenous amphotericin B and maintenance posaconazole after adjunctive drainage. This clinical experience highlights the efficacy of antifungal therapy alone in the treatment of potentially fatal cases of PM unsuitable for surgery. Abstract : We report an unusual case of pulmonary mucormycosis complicated by a large hydropneumothorax. The patient was successfully treated with liposomal amphotericin B and posaconazole following adjunctive drainage without surgical intervention, which has been seldom reported in the literature.